The Cardiac Fibroblast in heart failure – an inflammatory cell. (25th November 2020) - Thottakara, T; Dhople, V.M; Voss, S; Schoen, J; Voelker, U; Blankenberg, S; Westermann, D; Hammer, E; Lindner, D
Abstract: Introduction: Cardiac inflammation with subsequent remodeling of the extracellular matrix (ECM) with fibrosis formation is an important precursor of heart failure. In myocardial inflammation release of cytokines, such as TNF-α was previously linked to the development of fibrosis. However, their exact role in fibroblasts activation, leading to their transformation into myofibroblasts and ultimately fibrosis is unknown. Therefore, the purpose of this work was to study the secretome of isolated cardiac fibroblasts of heart failure patients in vitro. Methods and results: Human cardiac fibroblasts were obtained from endomyocardial biopsies of patients with reduced ejection fraction. Secretome- and gene expression analysis was performed on TNF-α (10 ng/ml) and TGF-β (5 ng/ml) treated and untreated fibroblasts. The analysis of the secretome in cell culture supernatant of these fibroblasts was performed by nano-LC-ESI tandem mass spectrometry. Subsequently, RNA was isolated from fibroblasts and expression analysis was performed using affymetrix gene chips and verified for the stimulation experiments using TaqMan. The secretome and gene expression studies are constistent regarding the most frequent ECM components. The proteins involved in the construction of the ECM accounted for 56% of the total protein intensity. The fibronectin represented the largest proportion of ECM proteins (50%), with collagens accounting for 29% and MMPs and TIMPs for approximately 5% and a small proportion of cytokines. In the secretome as well as in the gene expression, Il-6 and Il-8 showed the highest proportion of cytokines and type I as well as type IV (each approx. 40%) of collagens. MMP2, MMP1 and TIMP1 accounted for the largest proportion of MMPs and TIMPs. Stimulation with TGF-β and TNF-α led to changes in the composition of the cytokines and ECM proteins. After the stimulation with TNF-α, the proportion of cytokines increased from 3.1% to 6.6%, while the proportion of ECM proteins decreased slightly. Accordingly, after stimulation with TGF-β a well-known inductor of fibrosis, the proportion of collagens and other matrix proteins increased, while the proportion of cytokines decreased slightly. Conclusion: In this study, we identified the most abundant proteins of the ECM and demonstrated their expansion caused by TGF-β stimulation of fibroblasts. Surprisingly, TNF-α led to an increase of cytokines secreted by the fibroblasts with a minimal reduction of ECM proteins. Here, the differentiated regulation of the fibroblast in the transformation of the ECM could be seen. TNF-α stimulation demonstrated to increase gene expression of the cytokines in fibroblasts, which in turn maintain inflammation with chemotactic effect. Hence, cardiac fibroblasts seem to be supporting cells for cardiac inflammation. There seemed to be no pro-fibrotic effect. In this work we could show the pro-inflammatory role of the cardiac fibroblast upon inflammatory stimulation. Funding Acknowledgement: Type of funding source: None